“I am the Chair”: Women and Department Leadership in the Academy - Kruse, Sharon (Frontiers in Education, 2022)
The paucity of women in leadership roles in the academy has been the focus of the literature in higher education for several decades. The discussion has lamented how few women attain presidencies, chancellorships, or vice chancellor roles, that women of color experience even greater barriers to leadership attainment, and that women are likely to experience both a “glass ceiling” and a “glass cliff”. As a result, women often find themselves trapped in low-level managerial roles, unsupported when they do attain leadership positions, and underrepresented on powerful committees and in meaningful decision-making bodies. Drawing on data from a large study of the department chair, this qualitative study explores the experiences of twenty women who hold the position. Findings suggest that women department chairs continue to face ongoing gendered challenges to their leadership and that barriers to their success are still very much present in the academy. Coping with these challenges requires a balancing act within oneself, with others, and within the institution. Each challenge is then reflected in tensions that must be negotiated rather than resolved. Recommendations for structural and cultural changes are offered.